Reform of Islamic Family Law Through Gender-Sensitive Ijtihad: The Role of Female Judges in Indonesian Religious Courts - Ramdani Wahyu Sururie; Doli Witro; Irma Suryani; Abdul Mufti Albasyari; Muhammad Iqbal Zia Ulhaq; Ahmad Mundzir; Hayatul Islami (Jurnal Ilmiah Al-Syir'ah, 2026)
Historically, the rulings of Indonesian Religious Courts have critically shaped gender justice in family law; however, the specific contributions of female judges through their judicial reasoning remain under-explored in a systematic manner. This article aims to highlight female judges from a legal perspective, viewing them not merely from a passive legal standpoint but also emphasising their active role in reforming Islamic family law. This research employs a legal-empirical approach. Primary data consists of official copies of religious court rulings; the four rulings analysed were selected from cases between 2019 and 2024. In addition, primary data was also collected through in-depth interviews with three female judges from various regions in Indonesia: Sumatra, Java, and Eastern Indonesia. Secondary data was gathered from a literature review, which included academic articles, annual judicial reports, and legal textbooks. Data analysis was conducted using a qualitative approach, beginning with data condensation, followed by data presentation, and concluding with the findings. This study concludes that female judges play a role in the reform of Islamic family law through the appropriate interpretation of legal sources and the legal facts presented in court proceedings. Furthermore, the use of a gender-justice-based ijtihad approach to achieve gender equality between male and female judges requires a holistic approach. On the other hand, female judges also systematically link various legal sources and employ legal reasoning to uncover the deeper truth behind the facts, which is essential for justice and legal reform.